Reconstruction of the interior of the Saint Salvator abbey of Ename around 1290 - Carlotta Capurro; Dries Nollet; Daniel Pletinckx (Virtual Archaeology Review)
In this paper we outline the process of research about the reconstruction of the Saint Saviour abbey in Ename (Oudenaarde, Belgium) in the 13th century both in its architectural decoration and in its furnishing. The reason for the reconstruction is the creation of an educational game for the visitors of the Provincial Heritage Centre, built just next to the archaeological site of the abbey.